Pengaruh Penambahan Dinding Geser (Shear Wall) pada Waktu Getar Alami Fundamental Struktur Gedung - Astuti, Pinta (Semesta Teknika, 2015)
The structure of high-rise buildings should have sufficient stiffness so that no damage could harm users when earthquake occurred. The addition of shear wall structure is one way to increase stiffness of the building. This research is analyzing the capacity of structural elements and the influence of shear walls in high rise buildings, taking a case study at Mataram City Apartments and Condominium, Yogyakarta. The building consists of two towers. Analytical calculations in this research based on technical data field, quality of materials, and the results of structural analysis with SAP2000. After that, this research will calculate strength of the structure. The analysis based on SNI 03-2847-2002, SNI 03-1726-2002, and the Uniform Building Code (UBC) 1997 Chapter 16 on Requirements Design Structure. Three modification of the shear wall layouts in this research are use to understanding about the effect of adding shear walls to the natural vibration time.Â Â Based on the analysis and calculation, the structure has adequate capacity to support the load with the natural vibration period of 1.831 seconds. Maximum allowable vibration time by SNI 03-1726-2002 is 3.24 seconds, while the Uniform Building Code (UBC) is 1.698 seconds. First model can decrease the natural vibration period of 1.53 % to 1.80 seconds with a drift reduction of 11.35 % in the x axis and 35.27 % in y axis. The second model can decrease the natural vibration period by 5.08 % to be 1.73 seconds with drift reduction is 20.73 % the x axis, 39.31 % and y axis. The merged models have the natural vibration structure of 1.66 seconds